The effects of the oil price and oil price volatility on inflation in Turkey - Kose, Nezir; Unal, Emre (Pergamon-Elsevier Science Ltd, 2021)
The effects of the oil price and oil price volatility on inflation in Turkey were analyzed via a structural vector autoregression (SVAR) model, using monthly data covering the period between March 1988 and August 2019. The result of variance decomposition indicates that the effects of the oil price and oil price volatility on inflation were limited in the early months but increased over the subsequent months. The labor cost indicates the same -its effect on inflation was limited in the early months but became more significant later. The exchange rate constituted the largest source of changes in inflation, and its impact only slightly decreased in the latter part of the period. According to the result of impulse response functions, the responses of the oil price and exchange rate to inflation were significant in the early months. The response of inflation to labor cost became significant after a few months. The result of this research indicates that following stable economic policies, considering both monetary policy and fiscal policy, provides important dynamics for the control of inflation. Nevertheless, the oil price is an external factor for which alternative ways need to be found in order to reduce its inflationary effect. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Inflation; Oil price; Oil price volatility; Structural VAR